Ground Penetrating Radar for Monitoring Damage in Reinforced Concrete Bridges: A Reliable Tool for Structural Health Assessment - Olumuyiwa Falowo; Victor Oluwasegunfunmi; Ajiboye Babatunde; Olabisi Kunle (Computational Engineering and Physical Modeling)
Ground penetrating radar has been developed and is increasingly used in bridge system and roadway condition assessment. Thus, this study evaluates the effectiveness of GPR for assessing concrete bridge deck condition, and geological foundation characterization/anomaly detection, at Sobe – Owan Bridge along Akure – Benin highway. The study utilized several ground-coupled frequencies: 1500 MHz for deck assessment, and 500 MHz and 250 MHz for foundation characterization, along three traverses. The desired penetration depth and resolution informed the adopted frequencies. The obtained data was processed and interpreted, as profiles depicting the magnitude and arrival time of the reflections. The profiles detected zones with low amplitude (0 to -2048) at depth below the 10 ns mark, indicating the presence of probable deterioration, which is assumedly related (directly) to the amount of debonding/delamination which allows fluids to reach the deck rebar, and induce corrosion of the bridge deck reinforcement, leading to deterioration. Consequently, 30.5 % of the bridge deck reinforcement is currently deteriorated, while 69.5% is in good condition. In addition, minor discontinuity of the reflected/diffracted rays, which are likely void/cavity anomaly within the subsurface geology were detected. However, these zones are too minor to induce instability in the bridge foundation system, as the anomalies are not directly beneath the piers or foundation footings. Thus, a periodic assessment would be necessary to monitor these voids. The depth of these anomalous zones is still within the zone of active erosion, hence the zone could be induce by the moving water (scour).